Arterial Tissue Regeneration for Pediatric Applications: Inspiration From Up‐to‐Date Tissue‐Engineered Vascular Bypass Grafts. Issue 5 (4th April 2013) - Cittadella, Giorgio; de, Achala; Dee, Ryan; De Coppi, Paolo; Seifalian, Alexander M.
Abstract The need for a valid replacement for autologous tissues in vascular surgery has led to the development of tissue‐engineered vascular grafts (TEVGs). Currently, only three kinds of TEVG have been used in clinical trials: synthetic scaffold‐based TEVGs, self‐assembled grafts, and decellularized exogenous tissues. This review presents the current options in the construction of TEVG and the changes that have occurred in the design following the clinical experience while focusing on the potential for pediatric applications. The emerging trend in the field, which is also pertinent for pediatric applications, is a shift from the development of vascular analogues to implants composed of scaffolds with autologous cellular components. Designs of such implants are currently being fine‐tuned so that a natural, functional tissue can gradually take over the role of scaffolds to stimulate the host's regenerative capacity and maintain the physiological homeostasis.